Relevansi Nilai Informasi Akuntansi Pada Laba, Nilai Buku, dan Arus Kas Operasi: Kasus di Perbankan Indonesia - Hadinata, Sofyan (AKTSAR: Jurnal Akuntansi Syariah, 2020)
This study aims to examine the relationship between capital markets and accounting information in Indonesian banking. Specifically, this study examines the value relevance of earnings, book values, and operating cash flows. Using a sample of banks listed on the Indonesia Stock Exchange from 2014 to 2018, this study accommodates the documented accounting information in the context of developing markets using stock prices of four months after year-end as a dependent variable. Sampling using a purposive sampling method. This research obtained 35 companies used in this study sample. This study uses panel data regression techniques with the Generalized Least Square (GLS) analysis approach. This study indicates that earnings and book value statistically have a positive effect on stock prices. Meanwhile, operating cash flow has no statistical effect on stock prices. This study also shows that earnings more value-relevant than other variables.